Multi-Mode Antibacterial Strategies Enabled by Gene-Transfection and Immunomodulatory Nanoparticles in 3D-Printed Scaffolds for Synergistic Exogenous and Endogenous Treatment of Infections - Qu, Xinhua (Advanced materials (Deerfield Beach, Fla.), 2022)
© 2022 Wiley-VCH GmbH.